Preparation and application of small magnetic powder core with high-flux magnetic ring performance

By preparing small magnetic powder cores with high flux magnetic ring performance, the problems of large volume of traditional transcranial magnetic stimulators and large magnetic stimulation coils are solved, and a high-performance small magnetic powder core is realized. It is suitable for home cranial magnetic stimulation treatment and provides a more convenient and efficient depression treatment plan.

CN119852079AActive Publication Date: 2025-04-18HENAN KUNLUN PRECISION MEDICAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510262077.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-18
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

The traditional transcranial magnetic stimulator has limited its application potential in family scenarios due to its large size and large magnetic stimulation coils, and cannot meet the convenient and efficient treatment needs of patients with depression in a home environment.

Method used

A small magnetic powder core with high flux magnetic ring performance is used to prepare a small magnetic powder core with high magnetic permeability, low hysteresis loss, good insulation performance and excellent molding through specific raw material formulation and preparation processes, including raw material pretreatment, hybrid grinding, preforming, sintering, surface treatment and shell packaging. Combined with magnetic field polarization and mass detection, a small magnetic powder core with high permeability, low hysteresis loss, good insulation performance and excellent molding is prepared.

Benefits of technology

It realizes the high-performance preparation of small magnetic powder cores, has high magnetic field strength, high magnetic permeability and high stability, and is suitable for cranial magnetic stimulation treatment in family scenarios, expanding the application scope of transcranial magnetic stimulation treatment, and providing more flexible and efficient treatment options for patients with depression.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852079A_ABST
    Figure CN119852079A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soft magnetic materials, and discloses preparation and application of a small magnetic powder core with high-flux magnetic ring performance. The preparation method comprises the following steps: preparing ferric oxide, nickel oxide, zinc oxide, manganese zinc ferrite, carbonyl iron powder, iron-nickel alloy powder, iron-silicon-aluminum alloy powder, nano magnetic alloy particles, an additive, a lubricant, an insulating film material and a shell material in parts by weight, and carrying out raw material pretreatment, mixing, sintering, surface treatment, shell packaging, magnetic field polarization and quality detection. According to the small-sized magnetic powder core prepared according to the steps, lower loss factor and higher hardness can be maintained while higher density, magnetic conductivity, saturation flux density and Curie temperature can be realized, so that the formula and the preparation process disclosed by the invention are more suitable for preparing the high-performance small-sized magnetic powder core; the method is particularly applied to application scenes requiring high magnetic field intensity, high magnetic conductivity and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic materials, in particular to the preparation and application of a small magnetic powder core with high magnetic flux and magnetic ring performance. Background Art

[0002] As a common mental health problem, the treatment methods of depression have been continuously explored and innovated. Transcranial magnetic stimulation therapy has become a new trend in the treatment of depression with its advantages of being painless, non-invasive and green. However, traditional transcranial magnetic stimulators are mainly suitable for hospital environments due to their large size and large magnetic stimulation coils, which greatly limits their application potential in home scenarios. With the increasing demand for convenience and personalization in the treatment of depression, it is particularly important to develop small transcranial magnetic stimulation devices suitable for home use. Therefore, the design of a small magnetic powder core with high magnetic flux magnetic ring performance has become the key. The small magnetic powder core needs to achieve the miniaturization of the magnetic stimulation coil on the basis of ensuring the magnetic field strength, so as to meet the convenience requirements of home use, further expand the scope of application of transcranial magnetic stimulation therapy, and provide more flexible and efficient treatment options for patients with depression. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the shortcomings of the prior art, the present invention provides the preparation and application of a small magnetic powder core with high magnetic flux and magnetic ring performance. It has the advantages of high magnetic flux and magnetic ring performance and a small magnetic powder core, solving the problems of large size and large magnetic stimulation coil of traditional transcranial magnetic stimulators.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: Preparation of a small magnetic powder core with high magnetic flux magnetic ring performance, comprising the following steps:

[0007] Step 1, raw material preparation: prepare the formula weight parts of ferric oxide, nickel oxide, zinc oxide, manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder, nano magnetic alloy particles, additives, lubricants, insulating film materials and shell materials;

[0008] Step 2: Pretreatment of raw materials: pretreatment of ferric oxide, nickel oxide, zinc oxide and insulating film materials;

[0009] Step 3, mixing raw materials: mixing manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder and nano magnetic alloy particles, adding anhydrous ethanol, using a ball mill at a speed of 300-400rpm, mixing and grinding for 1.0-1.5 hours, then adding pretreated ferric oxide, nickel oxide and zinc oxide, continuing to mix and grind for 2.5-3.0 hours, and finally adding additives, mixing for 15-20 minutes to obtain a mixed powder;

[0010] Step 4: Pre-pressing: Spray lubricant on the inner surface of the pre-prepared mold, put the mixed powder into the mold, and pre-press the mixed powder into a green body at a pressure of 100-150 MPa;

[0011] Step 5, sintering: transfer the green body to a sintering furnace, and heat it to 950-1000°C at a rate of 5-10°C / min under the protection of nitrogen greater than 99.9%, keep it warm for 30-60 minutes, then continue to heat it to 1200-1250°C, and keep it warm for 1-1.5 hours;

[0012] Step 6: Surface treatment: Use electrostatic spraying process to cover the pre-treated insulating film material on the surface of the sintered green body, with a thickness of 2-4.5 μm;

[0013] Step 7: Shell packaging: add the shell material according to the formula ratio, inject it into the mold containing the blank, and cure it at a temperature of 75-80°C for 1.5-1.8 hours to form a 1-1.5mm shell, and finally obtain a small magnetic powder core;

[0014] Step 8: Magnetic field polarization: Place the small magnetic powder core in an external magnetic field for directional polarization to optimize the magnetic domain arrangement;

[0015] Step 9. Quality inspection: Conduct magnetic performance test, insulation performance test and physical performance test on small magnetic powder cores.

[0016] Preferably, the raw materials of the small magnetic powder core and their weight ranges are: ferric oxide 8% to 11%; nickel oxide 11% to 14%; zinc oxide 4% to 8%; manganese-zinc ferrite 7% to 10%; carbonyl iron powder 6% to 9%; iron-nickel alloy powder 9.5% to 13%; iron-silicon-aluminum alloy powder 12% to 14%; nano-magnetic alloy particles 5% to 10%; additives 0.3% to 0.5%; lubricant 0.5% to 1.1%; insulating film material 2.3% to 3.6%; shell material 5% to 6%.

[0017] Preferably, the particle sizes of the iron-nickel alloy powder and the iron-silicon-aluminum alloy powder are both controlled between -200 mesh and -400 mesh, and the particle size of the nano-magnetic alloy particles is controlled between 10-40 nm.

[0018] Preferably, the additive consists of samarium, neodymium, cobalt and nitrogen in a ratio of 1:2:3:2, and the lubricant consists of molybdenum disulfide and graphite in a ratio of 1:6.

[0019] Preferably, the insulating film material is made of polytetrafluoroethylene film.

[0020] Preferably, the shell material is made of epoxy resin.

[0021] Preferably, the raw materials of the small magnetic powder core and their weight proportions are: 8.5% ferric oxide; 12.5% ​​nickel oxide; 6% zinc oxide; 8.5% manganese-zinc ferrite; 7.5% carbonyl iron powder; 11% iron-nickel alloy powder; 13% iron-silicon-aluminum alloy powder; 6% nano-magnetic alloy particles; 0.4% additives; 0.8% lubricant; 3% insulating film material; and 5.8% shell material.

[0022] Preferably, the ferric oxide, nickel oxide and zinc oxide pretreatment process is as follows: ferric oxide, nickel oxide and zinc oxide are uniformly mixed, put into a furnace, and pre-calculated at a temperature of 850-950° C. for 1.5-2 hours.

[0023] Preferably, the insulating film material pretreatment process is: passivating the tetrafluoroethylene film for 10-15 minutes with a mixture of 0.1mol / L-0.5mol / L potassium permanganate solution and 0.01mol / L-0.2mol / L nitric acid in a volume ratio of 1:1, and then repairing the insulating layer with nano titanium oxide powder.

[0024] Preferably, the application of small magnetic powder cores with high magnetic flux and magnetic ring performance, the small magnetic powder cores made according to the above-mentioned preparation steps are used for cranial magnetic stimulation treatment of depression in home scenarios.

[0025] Compared with the prior art, the present invention provides the preparation and application of a small magnetic powder core with high magnetic flux magnetic ring performance, which has the following beneficial effects:

[0026] 1. The raw material formula of the present invention can prepare a small magnetic powder core with high magnetic permeability, low hysteresis loss, good insulation performance and excellent formability by strictly controlling the particle size of iron-nickel alloy powder, iron-silicon-aluminum alloy powder and nano-magnetic alloy particles. By adding the content of manganese-zinc ferrite and iron-nickel alloy powder to the raw materials and controlling the content of ferric oxide, the proportion of each component can be reasonably balanced, while achieving higher density, magnetic permeability, saturation magnetic induction intensity and Curie temperature, it can also maintain a low loss factor and a high hardness. Therefore, the formula and preparation process of the present invention are more suitable for the preparation of high-performance small magnetic powder cores, especially in application scenarios requiring high magnetic field strength, high magnetic permeability and high stability.

[0027] 2. The preparation process of the present invention reduces impurities and improves insulation performance by pre-sintering and surface passivating some raw materials at high temperature, and performs staged mixing and ball milling in the mixing stage to ensure uniform dispersion of the components. High-purity nitrogen protection and staged heating are used in the sintering stage to optimize the microstructure. When performing surface treatment, an electrostatic spraying process is used to accurately control the thickness of the insulating film. Finally, after the small magnetic powder core is manufactured, the performance of the small magnetic powder core is improved by optimizing the magnetic domain arrangement. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] See also Figure 1 , the preparation of a small magnetic powder core with high magnetic flux magnetic ring performance includes the following steps:

[0031] Step 1, raw material preparation: prepare the formula weight parts of ferric oxide, nickel oxide, zinc oxide, manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder, nano magnetic alloy particles, additives, lubricants, insulating film materials and shell materials;

[0032] Step 2: Pretreatment of raw materials: pretreatment of ferric oxide, nickel oxide, zinc oxide and insulating film materials;

[0033] Step 3, mixing raw materials: manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder and nano magnetic alloy particles are mixed, anhydrous ethanol is added, and mixed and ground for 1.0-1.5 hours at a rotation speed of 300-400rpm using a ball mill, and then the pretreated ferric oxide, nickel oxide and zinc oxide are added, and the mixed and ground is continued for 2.5-3.0 hours, and finally the additives are added and mixed for 15-20 minutes to obtain a mixed powder to ensure that each component is fully dispersed;

[0034] Step 4: Pre-pressing: Spray lubricant on the inner surface of the prepared mold, load the mixed powder into the mold, and pre-press the mixed powder into a green body at a pressure of 100-150 MPa to reduce mold adhesion;

[0035] Step 5, sintering: transfer the green body to a sintering furnace, and heat it to 950-1000°C at a rate of 5-10°C / min under the protection of nitrogen greater than 99.9%, keep it warm for 30-60 minutes, then continue to heat it to 1200-1250°C, and keep it warm for 1-1.5 hours;

[0036] Step 6: Surface treatment: Use electrostatic spraying process to cover the pre-treated insulating film material on the surface of the sintered green body, with a thickness of 2-4.5 μm;

[0037] Step 7: Shell packaging: Add the shell material according to the formula ratio, inject it into the mold containing the blank, and cure it at 75-80°C for 1.5-1.8 hours to form a 1-1.5mm shell, and finally obtain a small magnetic powder core to ensure biological safety;

[0038] Step 8: Magnetic field polarization: Place the small magnetic powder core in an external magnetic field for directional polarization to optimize the magnetic domain arrangement and increase the remanence;

[0039] Step 9. Quality inspection: Conduct magnetic performance test, insulation performance test and physical performance test on small magnetic powder cores.

[0040] Specifically, the particle sizes of the iron-nickel alloy powder and the iron-silicon-aluminum alloy powder are controlled between -200 mesh and -400 mesh, and the particle size of the nano-magnetic alloy particles is controlled between 10-40 nm.

[0041] Specifically, the additive consists of samarium, neodymium, cobalt, and nitrogen in a ratio of 1:2:3:2, and the lubricant consists of molybdenum disulfide and graphite in a ratio of 1:6.

[0042] Specifically, the insulating film material is composed of a polytetrafluoroethylene (PTFE) film.

[0043] Specifically, the shell material is made of epoxy resin.

[0044] Specifically, the raw materials of the small magnetic powder core and their weight proportions are: 8.5% ferric oxide; 12.5% ​​nickel oxide; 6% zinc oxide; 8.5% manganese-zinc ferrite; 7.5% carbonyl iron powder; 11% iron-nickel alloy powder; 13% iron-silicon-aluminum alloy powder; 6% nano-magnetic alloy particles; 0.4% additives; 0.8% lubricant; 3% insulating film material; and 5.8% shell material.

[0045] Specifically, the pretreatment process of ferric oxide, nickel oxide and zinc oxide is as follows: ferric oxide, nickel oxide and zinc oxide are mixed evenly, sent into a Ma furnace, and pre-burned at a temperature of 850-950°C for 1.5-2 hours to eliminate impurities and form a uniform ferrite phase.

[0046] Specifically, the pretreatment process of the insulating film material is as follows: a mixture of 0.1mol / L-0.5mol / L potassium permanganate solution and 0.01mol / L-0.2mol / L nitric acid in a volume ratio of 1:1 is used to passivate the tetrafluoroethylene (PTFE) film for 10-15 minutes, and then nano-titanium oxide powder is used to repair the insulating layer to improve the insulation performance.

[0047] Specifically, the application of small magnetic powder cores with high magnetic flux and magnetic ring performance, the small magnetic powder cores made according to the above preparation steps are used for cranial magnetic stimulation to treat depression in home scenarios.

[0048] Example 1

[0049] Specifically, the raw materials of the small magnetic powder core and their weight ranges are: 8% to 11% of ferric oxide; 11% to 14% of nickel oxide; 4% to 8% of zinc oxide; 7% to 10% of manganese-zinc ferrite; 6% to 9% of carbonyl iron powder; 9.5% to 13% of iron-nickel alloy powder; 12% to 14% of sendustine alloy powder; 5% to 10% of nano-magnetic alloy particles; 0.3% to 0.5% of additives; 0.5% to 1.1% of lubricant; 2.3% to 3.6% of insulating film material; 5% to 6% of shell material (the particle sizes of the iron-nickel alloy powder and the sendustine aluminum alloy powder are controlled between -200 mesh and -400 mesh, and the particle size of the nano-magnetic alloy particles is controlled between 10-40nm).

[0050] Comparative Example 1

[0051] Specifically, the raw materials of the small magnetic powder core and their weight ranges are: 8% to 11% ferric oxide; 11% to 14% nickel oxide; 4% to 8% zinc oxide; 7% to 10% manganese-zinc ferrite; 6% to 9% carbonyl iron powder; 9.5% to 13% iron-nickel alloy powder; 12% to 14% sendustine alloy powder; 5% to 10% nano-magnetic alloy particles; 0.3% to 0.5% additives; 0.5% to 1.1% lubricant; 2.3% to 3.6% insulating film material; 5% to 6% shell material (the particle size of the iron-nickel alloy powder, sendustine aluminum alloy powder and nano-magnetic alloy particles in Example 1 is not controlled).

[0052] The performance of the small magnetic powder cores prepared in Example 1 and Comparative Example 1 was tested, and the comparison results are shown in Table 1:

[0053] Table 1

[0054]

[0055]

[0056] Summary: The formula of Example 1 can prepare a small magnetic powder core with high magnetic permeability, low hysteresis loss, good insulation performance and excellent formability by strictly controlling the particle size of iron-nickel alloy powder, iron-silicon-aluminum alloy powder and nano-magnetic alloy particles. The optimized performance of the raw materials makes it more suitable for medical applications of cranial magnetic stimulation to treat depression in home scenarios.

[0057] Example 2

[0058] The raw materials of the small magnetic powder core and their weight proportions are: 8% ferric oxide; 12% nickel oxide; 6% zinc oxide; 8% manganese-zinc ferrite; 7% carbonyl iron powder; 11% iron-nickel alloy powder; 13% iron-silicon-aluminum alloy powder; 8% nano magnetic alloy particles; 0.4% additives; 0.8% lubricant; 3% insulating film material; and 5.4% shell material.

[0059] Comparative Example 2

[0060] The raw materials of the small magnetic powder core and their weight proportions are: 5% ferric oxide; 12% nickel oxide; 6% zinc oxide; 12% manganese-zinc ferrite; 7% carbonyl iron powder; 15% iron-nickel alloy powder; 13% iron-silicon-aluminum alloy powder; 8% nano-magnetic alloy particles; 0.4% additives; 0.8% lubricant; 3% insulating film material; 5.4% shell material (the content of manganese-zinc ferrite in Example 2 is increased to 12%, and the content of iron-nickel alloy powder is increased to 15%, and the content of ferric oxide is reduced to 5%).

[0061] Table 2

[0062]

[0063]

[0064] Summary: After increasing the content of manganese-zinc ferrite and iron-nickel alloy powder and reducing the content of ferric oxide in Comparative Example 2, its overall performance is still lower than that of Example 2, indicating that the reduction of ferric oxide in the material combination content will affect the overall performance, and simply increasing the content of manganese-zinc ferrite and iron-nickel alloy powder cannot improve the performance, but will lead to a decrease in performance. Example 2 can achieve higher density, magnetic permeability, saturation magnetic induction intensity and Curie temperature by reasonably balancing the proportions of each component, while maintaining a lower loss factor and higher hardness. Therefore, the formula and process of Example 2 are more suitable for the preparation of high-performance small magnetic powder cores, especially in application scenarios requiring high magnetic field strength, high magnetic permeability and high stability.

[0065] Example 3 and Comparative Example 3

[0066]

[0067]

[0068]

[0069] Summary: Example 3 reduces impurities and improves insulation performance by pre-sintering and surface passivating some raw materials at high temperature, and performs staged mixing and ball milling in the mixing stage to ensure uniform dispersion of the components. High-purity nitrogen protection and staged heating are used in the sintering stage to optimize the microstructure. During surface treatment, an electrostatic spraying process is used to accurately control the thickness of the insulating film. Finally, after the small magnetic powder core is manufactured, the performance of the small magnetic powder core is improved by optimizing the magnetic domain arrangement. Comparative Example 3 (traditional method) is not optimized in multiple key steps, resulting in lower material performance and failure to meet the requirements of high-performance small magnetic powder cores.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Preparation of small magnetic powder core with high magnetic flux magnetic ring performance, characterized in that: The following steps are involved: Step 1, raw material preparation: prepare the formula weight parts of ferric oxide, nickel oxide, zinc oxide, manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder, nano magnetic alloy particles, additives, lubricants, insulating film materials and shell materials; Step 2: Pretreatment of raw materials: pretreatment of ferric oxide, nickel oxide, zinc oxide and insulating film materials; Step 3, mixing raw materials: mixing manganese zinc ferrite, carbonyl iron powder, iron nickel alloy powder, iron silicon aluminum alloy powder and nano magnetic alloy particles, adding anhydrous ethanol, using a ball mill at a speed of 300-400rpm, mixing and grinding for 1.0-1.5 hours, then adding pretreated ferric oxide, nickel oxide and zinc oxide, continuing to mix and grind for 2.5-3.0 hours, and finally adding additives, mixing for 15-20 minutes to obtain a mixed powder; Step 4: Pre-pressing: Spray lubricant on the inner surface of the pre-prepared mold, put the mixed powder into the mold, and pre-press the mixed powder into a green body at a pressure of 100-150 MPa; Step 5, sintering: transfer the green body to a sintering furnace, and heat it to 950-1000°C at a rate of 5-10°C / min under the protection of nitrogen greater than 99.9%, keep it warm for 30-60 minutes, then continue to heat it to 1200-1250°C, and keep it warm for 1-1.5 hours; Step 6: Surface treatment: Use electrostatic spraying process to cover the pre-treated insulating film material on the surface of the sintered green body, with a thickness of 2-4.5 μm; Step 7: Shell packaging: add the shell material according to the formula ratio, inject it into the mold containing the blank, and cure it at a temperature of 75-80°C for 1.5-1.8 hours to form a 1-1.5mm shell, and finally obtain a small magnetic powder core; Step 8: Magnetic field polarization: Place the small magnetic powder core in an external magnetic field for directional polarization to optimize the magnetic domain arrangement; Step 9. Quality inspection: Conduct magnetic performance test, insulation performance test and physical performance test on small magnetic powder cores.

2. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 1, characterized in that: The raw materials of the small magnetic powder core and their weight ranges are: 8% to 11% ferric oxide; 11% to 14% nickel oxide; 4% to 8% zinc oxide; 7% to 10% manganese-zinc ferrite; 6% to 9% carbonyl iron powder; 9.5% to 13% iron-nickel alloy powder; 12% to 14% iron-silicon-aluminum alloy powder; 5% to 10% nano-magnetic alloy particles; 0.3% to 0.5% additives; 0.5% to 1.1% lubricant; 2.3% to 3.6% insulating film material; and 5% to 6% shell material.

3. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 2, characterized in that: The particle sizes of the iron-nickel alloy powder and the iron-silicon-aluminum alloy powder are both controlled between -200 mesh and -400 mesh, and the particle size of the nano-magnetic alloy particles is controlled between 10-40 nm.

4. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 2, characterized in that: The additive consists of samarium, neodymium, cobalt and nitrogen in a ratio of 1:2:3:2, and the lubricant consists of molybdenum disulfide and graphite in a ratio of 1:

6.

5. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 2, characterized in that: The insulating film material is made of polytetrafluoroethylene film.

6. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 2, characterized in that: The shell material is made of epoxy resin.

7. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 2, characterized in that: The raw materials of the small magnetic powder core and their weight proportions are: 8.5% ferric oxide; 12.5% ​​nickel oxide; 6% zinc oxide; 8.5% manganese-zinc ferrite; 7.5% carbonyl iron powder; 11% iron-nickel alloy powder; 13% iron-silicon-aluminum alloy powder; 6% nano-magnetic alloy particles; 0.4% additives; 0.8% lubricant; 3% insulating film material; and 5.8% shell material.

8. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 1, characterized in that: The ferric oxide, nickel oxide and zinc oxide pretreatment process is as follows: the ferric oxide, nickel oxide and zinc oxide are mixed evenly, and are put into a furnace for pre-calcining at a temperature of 850-950° C. for 1.5-2 hours.

9. The preparation of a small magnetic powder core with high magnetic flux and magnetic ring performance according to claim 1, characterized in that: The insulating film material pretreatment process is as follows: a mixture of 0.1mol / L-0.5mol / L potassium permanganate solution and 0.01mol / L-0.2mol / L nitric acid in a volume ratio of 1:1 is used to passivate the tetrafluoroethylene film for 10-15 minutes, and then the insulating layer is repaired with nano titanium oxide powder.

10. Application of small magnetic powder core with high magnetic flux magnetic ring performance, characterized in that, The small magnetic powder core made according to the preparation steps of claim 1 is used for cranial magnetic stimulation treatment of depression in home settings.

Citation Information

Patent Citations

  • Magnetic powder core material with stable magnetic permeability and low loss and preparation method thereof

    CN108335820A

  • Combined inductor and preparation mold and preparation method thereof

    CN114898964A

  • Loss characteristic negative temperature coefficient integrated inductor and preparation method thereof

    CN119252644A

  • High-frequency magnetic material, and method of manufacturing the high-frequency magnetic material

    CN1812006A

  • Magnetic-sheet manufacturing method

    JP2008251735A